Synopsis of the mosquitoes (Diptera: Culicidae) of Romania - Păstrav, Ioana-Raluca; Domșa, Cristian; Mihalca, Andrei Daniel (Zootaxa, 2020)
Mosquitoes (Diptera: Culicidae) are insects capable of transmitting various disease agents. They have a wide geographical range, with a higher diversity and distribution in the tropical and subtropical regions. In Romania, data on mosquito distribution are available mostly from the older literature and published in local journals; hence, it is inaccessible to the international scientific community. The aim of this review was to gather all the published data on mosquitoes in Romania by performing a comprehensive literature search, to create a publicly available georeferenced database for the distribution of mosquitoes and generate distribution maps to identify gaps in the knowledge of mosquito diversity and distribution in the country. The resultant database includes 1,509 unique records for 51 mosquito species representing seven genera: Aedes, Anopheles, Culex, Culiseta, Coquillettidia, Orthopodomyia and Uranotaenia. Knowledge of mosquito distributions is important for understanding the risks of mosquito-borne pathogens present in Romania, a country with high endemicity for various diseases, such as West Nile fever and dirofilariasis. The database also revealed important knowledge gaps, including the lack of data for the Carpathian Arch and the central part of the historical regions of Moldova and Oltenia. The gaps become more evident, as the presence and diversity of the vectors have not been studied in many areas where diseases caused by mosquito-borne pathogens are present. In conclusion, despite the numerous georeferenced records, large areas of Romania remain unexplored for the mosquito species composition, abundance and phenology. This review is a “call for action” for implementing active surveillance in the country.